Holmium promoted yttria-zirconia supported Ni catalyst for H2 production via dry reforming of methane. (9th November 2022) - Fakeeha, Anis Hamza; Patel, Rutu; El Hassan, Nissrine; Al-Zahrani, Salma A.; Al-Awadi, Abdulrhman S.; Frusteri, Leone; Bayahia, Hossein; Alharth, Abdulrahman I.; Al-Fatesh, Ahmed Sadeq; Kumar, Rawesh
Abstract: Herein, a series of 5NixHo/YZr (x = 1, 2, 3, 4, 5 wt%) materials, never reported before, were tested in DRM reaction and characterized using several techniques like Nitrogen physisorption, X-ray diffraction, UV–vis and RAMAN spectroscopies, High Resolution Transmission Electron Microscopy, H2 -Temperature Programmed Reduction, CO2 -Temperature Programmed De-adsorption and Thermogravimetry. The incorporation of Yttria in the structure modifies pore sizes and stabilizes cubic Zirconia phases, whereas the addition of Ho as a promotor brings stable cubic zirconia, stable cubic holmium zirconium oxide phase and a wide range of reducible NiO-interacted species. In particular, an optimum Ho loading of 4 wt%, characterized by a minimum bandgap, strong suppression of RWGS reaction and maximum amount of reducible NiO-interacted species allows to achieve 84.1% H2 yield and 84.1% CO yield constantly over 420-min time on stream. The least basic sites availability over 5Ni5Ho/YZr results into inferior catalyst performance. Graphical abstract: Image 1 Highlights: 5NixHo/YZr (x = 0–5 wt%) materials is reported first time and found Highly affective in DRM. 5Ni/YZr has rich basic profile but unstable monoclinic ZrO2 phase which results into 44% H2 -yield. Ho presence nurtures stable cubic holmium zirconium oxide phase & wide range reducible NiO-species. 5Ni4Ho/YZr catalyst is characterized by minimum bandgap & maximum reducible NiO-species. 1 wt%Ho, 2 wt%Ho, 3 wt%Ho and 2 wt%Ho show 74.6%, 76%, 78.58% and 84.1% H2 yield respectively.